Secular Trend and Acceleration: a Review of Problems. - Malinowski, Andrzej (Anthropological Review, 1977)
On the basis of information from literature, the author describes secular trends in modern man. Particular attention was paid to explained as well as still awaiting explanation questions concerning the acceleration of development, diseases, physical capacity, and problems of retarded involutionary changes in the senile organism. Theories explaining the phenomenon of the secular trend are presented together with a description of the practical consequences of those developmental changes.